Respuesta :
Answer:
[tex]\cos(A + B) = \frac{23}{265}[/tex]
Step-by-step explanation:
Given
[tex]\tan A=\frac{28}{45}[/tex]
[tex]\cos B=\frac{3}{5}[/tex]
Required
[tex]\cos(A+B)[/tex]
In trigonometry:
[tex]\cos(A+B) = \cos\ A\ cosB - sinA\ sinB[/tex]
We need to solve for cosA, sinA and sinB
Given that:
[tex]\tan A=\frac{28}{45}[/tex] and the tangent of an angle is a ratio of the opposite side (x) to the adjacent side (y),
So, we have:
[tex]x =28[/tex] and [tex]y = 45[/tex]
For this angle A, we need t calculate its hypotenuse (z).
Using Pythagoras,
[tex]z^2 = x^2 + y^2[/tex]
[tex]z = \sqrt{x^2 + y^2[/tex]
[tex]z = \sqrt{28^2 + 45^2[/tex]
[tex]z = \sqrt{2809[/tex]
[tex]z = 53[/tex]
From here, we can calculate sin and cos A
[tex]\sin A= \frac{opposite}{hypotenuse}[/tex] and [tex]\cos A= \frac{adjacent}{hypotenuse}[/tex]
[tex]\sin A= \frac{x}{z}[/tex]
[tex]\sin A= \frac{28}{53}[/tex]
[tex]\cos A= \frac{y}{z}[/tex]
[tex]\cos A= \frac{45}{53}[/tex]
To angle B.
Give that
[tex]\cos B=\frac{3}{5}[/tex] and the cosine of an angle is a ratio of the adjacent side (a) to the hypotenuse side (c),
So, we have:
[tex]a = 3[/tex] and [tex]b = 5[/tex]
For this angle B, we need to calculate its opposite (b).
Using Pythagoras,
[tex]c^2 = a^2 + b^2[/tex]
[tex]5^2 = 3^2 + b^2[/tex]
[tex]25 = 9 + b^2[/tex]
Collect like terms
[tex]b^2 = 25 - 9[/tex]
[tex]b^2 = 16[/tex]
[tex]b = \sqrt{16[/tex]
[tex]b = 4[/tex]
From here, we can calculate sin B
[tex]\sin B= \frac{opposite}{hypotenuse}[/tex]
[tex]\sin B = \frac{b}{c}[/tex]
[tex]\sin B = \frac{4}{5}[/tex]
Recall that:
[tex]\cos(A+B) = \cos\ A\ cosB - sinA\ sinB[/tex]
and
[tex]\cos B=\frac{3}{5}[/tex] [tex]\sin B = \frac{4}{5}[/tex] [tex]\sin A= \frac{28}{53}[/tex] [tex]\cos A= \frac{45}{53}[/tex]
[tex]\cos(A + B) = \frac{45}{53} * \frac{3}{5} - \frac{28}{53} * \frac{4}{5}[/tex]
[tex]\cos(A + B) = \frac{135}{265} - \frac{112}{265}[/tex]
[tex]\cos(A + B) = \frac{135-112}{265}[/tex]
[tex]\cos(A + B) = \frac{23}{265}[/tex]
The value of [tex]\cos (A+B)[/tex] is [tex]-\frac{96}{265}[/tex].
Trigonometrically speaking, the sine, cosine and tangent of an angle are described by the following formulas:
[tex]\sin \theta = \frac{y}{\sqrt{x^{2}+y^{2}}}[/tex] (1)
[tex]\cos \theta = \frac{x}{\sqrt{x^{2}+y^{2}}}[/tex] (2)
[tex]\tan \theta = \frac{y}{x}[/tex] (3)
Where:
- [tex]\theta[/tex] - Angle, in sexagesimal degrees.
- [tex]x[/tex] - Adjacent leg.
- [tex]y[/tex] - Opposite leg.
And we have the following trigonometric identity for the cosine of the sum of angles:
[tex]\cos (A+B) = \cos A\cdot \cos B - \sin A \cdot \sin B[/tex] (4)
By (1) and (2), we rewrite (4):
[tex]\cos (A+B) = \frac{x_{A}\cdot x_{B}}{\sqrt{x_{A}^{2}+y_{A}^{2}}\cdot \sqrt{x_{B}^{2}+y_{B}^{2}}} - \frac{y_{A}\cdot y_{B}}{\sqrt{x_{A}^{2}+y_{A}^{2}}\cdot \sqrt{x_{B}^{2}+y_{B}^{2}}}[/tex]
If we know that [tex]x_{A} = 28[/tex], [tex]y_{A} = 45[/tex], [tex]x_{B} = 3[/tex] and [tex]y_{B} = 4[/tex], then the cosine for the sum of angles is:
[tex]\cos (A+B) = \frac{28\cdot 3}{\sqrt{28^{2}+45^{2}}\cdot \sqrt{3^{2}+4^{2}}}-\frac{45\cdot 4}{\sqrt{28^{2}+45^{2}}\cdot \sqrt{3^{2}+4^{2}}}[/tex]
[tex]\cos (A+B) = -\frac{96}{265}[/tex]
The value of [tex]\cos (A+B)[/tex] is [tex]-\frac{96}{265}[/tex].
We kindly invite to check this question on trigonometric identities: https://brainly.com/question/24836845